Nested-channel for on-demand alternation between electrospray ionization regimes. Issue 5 (22nd December 2020) - Li, Mengtian; Li, Huishan; Allen, Nicholas R.; Wang, Taoqing; Li, Linfan; Schwartz, Jae; Li, Anyin
Abstract : Nested electrospray ionization alternates on-demand between microscale main-channel and nanscale sub-channels. Abstract : On-demand electrospray ionization from different liquid channels in the same emitter was realized using filamented capillary and gas phase charge supply. The solution sub-channel was formed when back-filling solution to the emitter tip by capillary action along the filament. Gas phase charge carriers were used to trigger electrospray ionization from the solution meniscus at the tip. The meniscus at the tip opening may be fully filled or partially empty to generate electrospray ionization in main-channel regime and sub-channel regime, respectively. For emitters with 4 μm tip opening, the two nested electrospray (nested-ESI) channels accommodated ESI flow rates ranging from 50 pL min −1 to 150 nL min −1 . The platform enabled on-demand regime alternations within one sample run, in which the sub-channel regime generated smaller charged droplets. Ionization efficiencies for saccharides, glycopeptide, and proteins were enhanced in the sub-channel regime. Non-specific salt adducts were reduced and identified by regime alternation. Surprisingly, the sub-channel regime produced more uniform responses for a peptide mixture whose relative ionization efficiencies were insensitive to ESI conditions in previous picoelectrospray study. The nested channels also allowed effective washing of emitter tip for multiple sampling and analysis operations.